Gamification in the Learning Evaluation on Students' Learning Outcomes of English Education Students - Harmilawati; Sabaruddin; Kareba, Andi Muammar; Khaerunnisa; Jusmaniar (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This research sets the goals to find out the form of gamification in the learning evaluation on the learning outcomes of English Education students and the effectiveness of using gamification in the learning evaluation on the learning outcomes of English Education students. English Book Grammar Application and Cue Card used as the media in implementing the gamification. Quantitative research with pre-experimental was conducted in this research. The research was conducted at English Education Study Program Islamic Institute of Muhammadiyah (IAIM) Sinjai and English Education Study Program of Makassar Islamic University (UIM). The sample of this research were 25 students from IAIM Sinjai and UIM by using purposive sampling technique. Test and documentation techniques were combined to obtain the data. The collected data then analyzed by descriptive statistics and inferential statistic. The result showed that: (1) the form of gamification in the learning evaluation of English Education students using the English Book Grammar application and Cue Card is like playing the game with its components, such as grouping the students, explaining the rules, giving question to the students, the students competing answer the question by using English Book Grammar App and Cue Card, scoring the result, and giving rewards to the winner. (2) the use of gamification in the learning evaluation is effective on the learning outcomes of English Education students. It can be seen from the result of data analysis by using t-test where sig. 0,000 < 0,05 means H1 is accepted.